Surgical treatment of secondary hyperparathyroidism - Takagi, Hiroshi; Kawai, Machio; Uchida, Kazuharu; Kano, Tadayuki; Tominaga, Yoshihiro; Yamada, Nobuo (Journal of Japanese Society for Dialysis Therapy, 1986)
Seventy patients with chronic renal failure underwent surgical therapy for secondary hyperparathyroidism; the first 20 received subtotal parathyroidectomy and the other 50 total parathyroidectomy and parathyroid autotransplant in the forearm. In 12 of the 20 subtotal parathyroidectomy cases, identification and removal of four glands were possible. Among the 50 total parathyroidectomy and autotransplantation cases, five parathyroid glands were removed from one patient and four from the other 49. Preoperative image diagnosis was valuable for locating ectopic and supernumerary parathyroid glands and differentiating swollen parathyroid glands from tyroid tumors, which are a frequent complication. After the operation, serum calcium decreased rapidly, especially in the patients with severe bone change, and adequate calcium replacement therapy was necessary. Two of the patients complained of persistent hyperparathyroidism postoperatively, and we considered the possibility of supernumerary glands in the neck. The grafted tissues in all cases functioned well: reimplantation of cryopreserved parathyroid tissue was unnecessary, and osteomalacia after parathyroidectomy was not seen clinically. Two of the 20 subtotal parathyroidectomy patients were submitted to re-exploration of the neck because of recurrence. Recurrence was also diagnosed in four of the 50 total parathyroidectomy and autotransplantation patients, and one of these four underwent excision of the transplanted parathyroid tissues under local anesthesia. In our experience, total parathyroidectomy and autotransplantation is an adequate treatment for secondary hyperparathyroidism. This procedure has the advantage of ensuring sufficient parathyroid function. Furthermore, parathyroid function can be controlled by additional transplantation of cryopreserved tissue or by excision of grafted tissue under local anesthesia.